Métabolisme urbain et quartiers péricentraux dans la métropolisation. L’exemple du quartier de Saint-Michel à Montréal - Violaine Jolivet; Marie-Noëlle Carré (Cybergeo)
Debates on territorial marketing at an international scale pay more and more attention to quality of life and urban sustainability as competitive advantages to attract international investments. Yet few studies have provided insights into the entanglements between cities’ globalization and urban metabolism at the local scale. This paper aims to understand their long-term impact on the transformations of Saint-Michel, an inner suburb in Montréal (Quebec, Canada). Local extraction (quarries) and accumulation (garbage) have always had a significant place in the more general shaping of the metropolitan area. Those issues question the economic, political and environmental challenges of the globalization process through a situated and contextualized point of view.